Soil Survey in Identifying Priority Areas for Soil Conservation with Special Reference to Chambal Catchment - Satyanarayana, KVS (Journal of Soil and Water Conservation, 2022)
The catchment of Chambal river above Gandisagar dam -has an area of about 8700 square miles. The very vastness of the catch-ment and the many limitations--financial and physical—in implementing conservation pro-grammes, necessitate an assessment of erosion and fixation of priority tracts for scheduling conservation activities within the scope of a long range programme. It is in this context that reconnaissance soil survey in Chambal Catchment could prove to be a valuable tool. The subcommittee constituted by the Planning Commission to study the progress of soil conservation work in River Valley Project areas, recommended4hat a soil survey of the entire Chambal ,catchment should be com-pleted within a period of five years.